Gingival hyperplasia: anaesthetic implications - Chahar, Shikha; Saxena, Anupriya (International Journal of Research in Medical Sciences, 2017)
Gingival hyperplasia can be divided in four sub categories: Inflammatory, hereditary, drug induced and associated with systemic causes. It can be localized or generalized. Gingival hyperplasia can cause difficulty in swallowing, speech and mastication, delayed dentition and poor aesthetics. Maintenance of oral hygiene plays a major role in all varieties of gum hyperplasia especially in inflammatory types, which poses a great challenge to anaesthesiologists as the gums are friable, tender and prone to bleed. We report successful management of a child posted for gingivectomy under general anaesthesia.